Assessment of heavy metals with ecological risk of soils in the industrial vicinity of Tangail district, Bangladesh - Proshad, Ram; Islam, Md. Saiful; Kormoker, Tapos (International Journal of Advanced Geosciences, 2018)
This study was conducted to assess the ecological risk of heavy metals in soils collected from the industrial vicinity of Tangail district in Bangladesh. In this study, the levels of six heavy metals namely chromium (Cr), nickel (Ni), copper (Cu), arsenic (As), cadmium (Cd), and lead (Pb) in 15 sampling sites around the industrial vicinity of Tangail district in Bangladesh were assessed. The mean concentration of Cr, Ni, Cu, As, Cd and Pb in studied soils were 11.56, 23.92, 37.27, 6.11, 2.01, and 17.46 mg/kg, respectively. Certain indices, including the enrichment factor (EF), contamination factor (Cif), geoaccumulation index (Igeo), pollution load index (PLI), toxic unit analysis, and principal component analysis (PCA) were used to assess the ecological risk. The enrichment factor of all the studied metals for all sampling sites were in the descending order of Cd > Cu > As > Pb >Ni > Cr. The contamination factor values revealed that the studied soils were highly impacted by Cd. The pollution load index (PLI) values of Cd were higher than 1, indicating the progressive deterioration of soil due to Cd contamination. In the context of potential ecological risk (PER), soils from all sampling sites showed moderate to very high potential ecological risk.